High HER2/Centromeric Probe for Chromosome 17 Fluorescence In Situ Hybridization Ratio Predicts Pathologic Complete Response and Survival Outcome in Patients Receiving Neoadjuvant Systemic Therapy With Trastuzumab for HER2-Overexpressing Locally Advanced Breast Cancer. (9th December 2015) - Kogawa, Takahiro; Fouad, Tamer M.; Liu, Diane D.; Wu, Jimin; Shen, Yu; Masuda, Hiroko; Fujii, Takeo; Chavez-MacGregor, Mariana; Alvarez, Ricardo H.; Hortobágyi, Gabriel N.; Valero, Vicente; Ueno, Naoto T.
Abstract: Background: The present study was performed to determine whether the human epidermal growth factor receptor-related 2 (HER2)/centromeric probe for chromosome 17 fluorescence in situ hybridization (FISH) ratio is a predictor of a pathologic complete response (pCR), recurrence-free survival (RFS), and/or overall survival (OS) in patients receiving neoadjuvant systemic treatment (NST) with trastuzumab (NST-T) for HER2+ locally advanced breast cancer (LABC). Patients and Methods: The present retrospective study included 555 patients with HER2+ LABC who had undergone NST and definitive surgery (1999–2012); 373 had concurrently received trastuzumab. HER2-positivity was considered present with an immunohistochemical score of 3+ and/or HER2 FISH ratio of ≥2.0. We used logistic regression analysis and Cox proportional hazard modeling to determine whether a high HER2 FISH ratio, either as a continuous variable or with a cutoff of ≥7.0, would predict for pCR (no invasive disease in the breast and no tumor in the ipsilateral axillary lymph nodes), RFS, and/or OS. Results: The pCR group's median HER2 FISH ratio was significantly higher than that of the non-pCR group (6.4 vs. 5.2; p = .003). The logistic regression model demonstrated that the independent predictors of pCR included a high HER2 FISH ratio as a continuous variable ( p = .04). The multicovariate Cox proportional hazard model showed that a high HER2 FISH ratio (with a cutoff of ≥7.0 or as a continuous variable) was a significant prognostic indicator of longer RFS time ( p = .047 and p = .04, respectively). Similarly, a high HER2 FISH ratio of ≥7.0 was associated with longer OS ( p = .06). Conclusion: A high HER2 FISH ratio is a predictor of pCR in patients with HER2+ LABC who receive NST-T. Abstract : The present study has demonstrated that a high human epidermal growth factor receptor 2-related fluorescence in situ hybridization ratio is a significant predictive factor for a pathologic complete response and recurrence-free survival, with a favorable tendency to predict overall survival in patients with locally advanced breast cancer receiving neoadjuvant systemic treatment with trastuzumab.